2022
DOI: 10.1152/jn.00221.2021
|View full text |Cite
|
Sign up to set email alerts
|

Contextual saccade adaptation induced by sequential saccades

Abstract: Saccade adaptation is the gradual adjustment of saccade end point to maintain spatial accuracy. Contextual adaptation refers to a situation in which the adaptation-related change in saccade end point is contingent on the behavioral context in which the saccade is made. For example, in some situations, the same saccade to the same retinotopic location can be simultaneously adapted in opposite directions depending on the context in which it is made. Saccade adaptation has traditionally been studied in isolated m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…The vermis is a longitudinally narrow structure within the cerebellum [35]. Saccade adaptation is a process in which the cerebellar oculomotor system reduces saccadic error during the saccadic process [36]. The study has reported that lobules VI and VII of the vermis, also referred to as the oculomotor vermis, play a crucial role in saccade adaptation [37].…”
Section: Discussionmentioning
confidence: 99%
“…The vermis is a longitudinally narrow structure within the cerebellum [35]. Saccade adaptation is a process in which the cerebellar oculomotor system reduces saccadic error during the saccadic process [36]. The study has reported that lobules VI and VII of the vermis, also referred to as the oculomotor vermis, play a crucial role in saccade adaptation [37].…”
Section: Discussionmentioning
confidence: 99%